Web-Based System Enhances Extracurricular Management Efficiency in Educational Institutions: Sistem Berbasis Web Meningkatkan Efisiensi Pengelolaan Ekstrakurikuler di Institusi Pendidikan - Hidayat, Fahri Fauzi; Rahmawati, Yunianita (Indonesian Journal of Law and Economics Review, 2024)
Background: The advancement of information technology has significantly influenced educational management, particularly in managing extracurricular activities within schools. Specific Background: Traditional methods of managing these activities often lead to time-consuming processes and ineffective communication, highlighting the need for a more efficient system. Knowledge Gap: While various management systems exist, few specifically address the challenges faced in managing extracurricular activities effectively and transparently. Aims: This research aims to develop and implement a web-based Extracurricular Management Information System (SIMAK) to enhance efficiency and transparency in managing extracurricular activities. Results: Utilizing Agile methodology with the Scrum model and the Laravel framework, the study successfully developed the SIMAK application, which supports activity registration, schedule management, attendance tracking, and student assessments. The implementation of SIMAK resulted in improved administrative efficiency, streamlined processes, and increased transparency in information access for administrators, coaches, and students. Novelty: This study presents a unique approach to extracurricular management by leveraging modern technology and methodologies to address existing inefficiencies in educational settings. Implications: The findings suggest that the SIMAK application not only enhances the management of extracurricular activities but also encourages greater student participation and provides schools with better data for decision-making. Overall, the application significantly contributes to optimizing students' educational experiences outside the classroom, promoting a more organized and transparent approach to extracurricular management. Highlights: Efficiency: Streamlines registration and scheduling processes for extracurricular activities. Transparency: Improves information access for all users involved. Engagement: Increases student participation in extracurricular activities. Keywords: Extracurricular Management, Information System, Agile Methodology, Transparency, Education Technology